Gut symbiotic bacteria stimulate insect growth and egg production by modulating hexamerin and vitellogenin gene expression. (April 2017) - Lee, Jun Beom; Park, Kyoung-Eun; Lee, Seung Ah; Jang, Seong Han; Eo, Ho Jeong; Jang, Ho Am; Kim, Chan-Hee; Ohbayashi, Tsubasa; Matsuura, Yu; Kikuchi, Yoshitomo; Futahashi, Ryo; Fukatsu, Takema; et al.
Abstract: Recent studies have suggested that gut symbionts modulate insect development and reproduction. However, the mechanisms by which gut symbionts modulate host physiologies and the molecules involved in these changes are unclear. To address these questions, we prepared three different groups of the insect Riptortus pedestris : Burkholderia gut symbiont-colonized (Sym) insects, Burkholderia -non-colonized (Apo) insects, and Burkholderia -depleted (Sym Burk- ) insects, which were fed tetracycline. When the hemolymph proteins of three insects were analyzed by SDS-PAGE, the hexamerin-α, hexamerin-β and vitellogenin-1 proteins of Sym-adults were highly expressed compared to those of Apo- and Sym Burk- -insects. To investigate the expression patterns of these three genes during insect development, we measured the transcriptional levels of these genes. The hexamerin-β gene was specifically expressed at all nymphal stages, and its expression was detected 4–5 days earlier in Sym-insect nymphs than that in Apo- and Sym Burk- -insects. However, the hexamerin-α and vitellogenin-1 genes were only expressed in adult females, and they were also detected 6–7 days earlier and were 2-fold higher in Sym-adult females than those in the other insects. Depletion of hexamerin-β by RNA interference in 2nd instar Sym-nymphs delayed adult emergence, whereas hexamerin-α and vitellogenin-1 RNA interference in 5th instar nymphs caused loss of color of the eggs of Sym-insects. These results demonstrate that the Burkholderia gut symbiont modulates host development and egg production by regulating production of these three hemolymph storage proteins. Highlights: Gut symbionts are known to modulate host development and egg production. Expressions of hemolymph proteins are specifically changed by presence of gut symbiont. Burkholderia symbiont promotes the host's development and fecundity via symbiosis-affected host molecule. This study describes molecular cross-talk between insects and gut symbionts.